Stigma and coping in peruvians adults with HIV - Horna Gomez, Maria Jose (2025)
The study explored the relationship between perceived stigma and coping strategies used in adults with HIV/AIDS. This was a cross-sectional correlational project. A total of 350 patients from a public hospital in Lima of different genders (M: 254, F: 92, NB: 4) aged between 18 and 55 years (M: 37, SD= 10.86), and, with treatment times between 6 months and 30 years, voluntarily participated. A sociodemographic form, the HIV Stigma Scale to explore stigma and the COPE questionnaire to measure coping were applied. Heterosexual sexual orientation was the majority of the cases (54 %), more than 30 % considered themselves as the main social support and 37.4% had university education. Stigma was high (28.6 %) to moderate (71.4 %), 50 % of the cases were concerned about their diagnosis being revealed, and the most used coping strategy was problem-focused (65.1 %). A negative and highly significant relationship was found between variables (r=.205, p<.001), with a small effect size. In particular, the emotion-focused strategy, which is the most widely used, has a small effect on stigma (r=.160). It is concluded that the strength of the relationship between variables is low, so it is necessary to consider complementary variables such as social support, resilience, or self-efficacy. In addition, it is essential to implement psychoeducational and awareness-raising interventions aimed at the Peruvian population to prevent discriminatory acts based on this health condition, regardless of sex, gender, or sexual orientation.